Cyber Public Relations dalam Klub Sepakbola Di Indonesia: Studi Pada Persija Jakarta - Muhammad Andrya Surya Putra; Faridhian Anshari (Fakultas Ilmu Komunikasi Universitas Pancasila, 2016)
Technological developments make more and more public relations practitioners who utilize the Internet as a medium of delivery and dissemination of information, without exception the football club based company that is Persija Jakarta. Cyber public relations is a term of public relations activity in an effort to convey information to the public. This study aims to determine the strategies used public relations Persija in applying cyber public relations through the website and social media accounts twitter owned club Persija Jakarta as an effort to disseminate information to the public. This study uses the concept of cyber public relations and the utilization of social media and websites. This research is done by using qualitative approach. This research data retrieval technique through in-depth interview with public relations management Persija club, documentation and observation. The results showed that public relations Persija exploit the concept of cyber public relations in conveying information to the public through websites and social media twitter with the maximum. Public relations Persija realize with the implementation of the concept of cyber public relations through websites and social media twitter is very easy in delivering information widely and quickly to the public. In addition, by maximizing online public relations activity is able to form a positive image of football club Persija Jakarta.